2018
DOI: 10.1016/j.celrep.2018.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Cell-of-Origin DNA Methylation Signatures Are Maintained during Colorectal Carcinogenesis

Abstract: Colorectal adenomas are precursor lesions of colorectal cancers and represent clonal amplifications of single cells from colonic crypts. DNA methylation patterns specify cell-type identity during cellular differentiation and, therefore, provide opportunities for the molecular analysis of tumors. We have now analyzed DNA methylation patterns in colorectal adenomas and identified three biologically defined subclasses that describe different intestinal crypt differentiation stages. Importantly, colorectal carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 62 publications
(82 reference statements)
5
56
0
Order By: Relevance
“…Moreover, the cell of origin for APC initiated polyps and BRAF initiated polyps is hypothesized to differ. APC initiated lesions adhere to the "top-down" model 44 , whereas BRAF mutant lesions are initiated in the stem compartment 45 . Methylation profiling of BRAF mutant and APC mutant cancers confirmed this model, and showed that BRAF mutant cancers had a methylation profile reminiscent of the intestinal stem cell 45(p) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cell of origin for APC initiated polyps and BRAF initiated polyps is hypothesized to differ. APC initiated lesions adhere to the "top-down" model 44 , whereas BRAF mutant lesions are initiated in the stem compartment 45 . Methylation profiling of BRAF mutant and APC mutant cancers confirmed this model, and showed that BRAF mutant cancers had a methylation profile reminiscent of the intestinal stem cell 45(p) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite all the aforementioned alterations and the fact that mutations in DNA methylation writers and erasers have been described in diverse tumors (Simó -Riudalbas and Esteller, 2014), recent studies support the notion that cancer methylomes maintain a substantial part of the DNA methylation patterns from their cells-of-origin (Bormann et al, 2018;Oakes et al, 2016;Queiró s et al, 2016). Considering the heterogeneity observed in the methylomes of different cell types (Kundaje et al, 2015) and the potential of DNA methylation for tumor stratification (Capper et al, 2018;Pajtler et al, 2015), this can be highly valuable in the framework of precision oncology.…”
Section: Dna Methylation Deregulation In Epidermal Cancersmentioning
confidence: 99%
“…To ensure consistency of data processing, we only compared our samples with publically accessible samples with raw idat files. GSE68060, GSE68838, GSE77954, GSE77965, GSE81211, GSE101764, GSE107352, and GSE75546 were collected from GEO while E-MTAB-6450 was collected from ArrayExpress [43][44][45][46][47][48] (Additional file 1: Table S6). Some cell line samples and metastatic cancer samples were removed upon further study.…”
Section: Public Datasets and Processingmentioning
confidence: 99%